2021
DOI: 10.1001/jamadermatol.2021.0007
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis and Academic Achievement—More to Learn

Abstract: Education is one of the strongest factors associated with longterm health and well-being. 1 Chronic health conditions can affect multiple aspects of a child's education, including school readiness, attention, learning, school experience and engagement, attendance, test scores, and graduation rates. Moreover, the consequences of chronic illness may persist even after the child's health has recovered. 2 Interventions designed to address the unique challenges of chronic health conditions can have important and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Children with severe AD are known to have lower achievements in school than non-DA children. 22 In this study, disturbed sleep quality was found to be more frequent in the AD group, as measured by CSHQ score. The mean and standard deviation of melatonin levels in the case and control groups were 320.18±49.92 and 383.78 ±74.53 pg/mL, respectively.…”
Section: Discussionsupporting
confidence: 47%
“…Children with severe AD are known to have lower achievements in school than non-DA children. 22 In this study, disturbed sleep quality was found to be more frequent in the AD group, as measured by CSHQ score. The mean and standard deviation of melatonin levels in the case and control groups were 320.18±49.92 and 383.78 ±74.53 pg/mL, respectively.…”
Section: Discussionsupporting
confidence: 47%
“…The prevalence of autism spectrum disorders (ASD) is approaching 2% in populations of all racial, ethnic and socioeconomic groups, with a fourfold male predominance www.videleaf.com (https://www.tacanow.org/family-resources/latest-autismstatistics-2/ and https://www.cdc.gov/ncbddd/autism/data.html). Autism is diagnosed when a patient demonstrates deficits in social interactions; a lack of social or emotional reciprocity; and learning disabilities [1]. While the diagnosis of ASD is not firmly established until 24 months of age, abnormalities in fMRI scans; preferences for geometric patterns; aberrant social communications; changes in fine motor skills; and/or characteristic eye movements can often be detected as early as 6 months of age [2,3].…”
Section: Introductionmentioning
confidence: 99%